2023
DOI: 10.3389/fendo.2023.1153909
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anoikis-based molecular heterogeneity in pancreatic cancer and pancreatic neuroendocrine tumor and its association with tumor immune microenvironment and metabolic remodeling

Abstract: BackgroundAccumulating evidence suggests that anoikis plays a crucial role in the onset and progression of pancreatic cancer (PC) and pancreatic neuroendocrine tumors (PNETs); nevertheless, the prognostic value and molecular characteristics of anoikis in cancers are yet to be determined.Materials and methodsWe gathered and collated the multi-omics data of several human malignancies using the TCGA pan-cancer cohorts. We thoroughly investigated the genomics and transcriptomics features of anoikis in pan-cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, anoikis is closely related to the TIME. Li et al [ 31 ] observed a positive correlation between anoikis scores and macrophage levels, as well as para-inflammation, in pancreatic cancer. Conversely, they found a negative correlation between anoikis scores and tumor-infiltrating lymphocytes (TIL) and Th1 levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, anoikis is closely related to the TIME. Li et al [ 31 ] observed a positive correlation between anoikis scores and macrophage levels, as well as para-inflammation, in pancreatic cancer. Conversely, they found a negative correlation between anoikis scores and tumor-infiltrating lymphocytes (TIL) and Th1 levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 31 ] observed a positive correlation between anoikis scores and macrophage levels, as well as para-inflammation, in pancreatic cancer. Conversely, they found a negative correlation between anoikis scores and tumor-infiltrating lymphocytes (TIL) and Th1 levels [ 31 ]. According to the report by Xiao et al [ 32 ], in cases of colorectal cancer, there was a positive relationship observed between the risk score and regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Then the violin plots of MAPK scores were constructed and the survival curves were plotted to explore the survival discrepancies among these three clusters. Following a methodology similar to previous studies [ 17 , 18 ], we curated a selection of classical immune pathways, metabolic pathways, and cell death pathways. Initially, we computed pathway scores using the “gsva” package, providing a measure of each pathway’s activity.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the modulation of DNA methylation, histone acetylation, and histone methylation has shown potential in enhancing the efficacy of immune checkpoint inhibitors. Additionally, it can induce a transformation of tumor cell clusters from those associated with a poorer prognosis, a heightened expression of oncogenes, and limited immune cell infiltration to clusters that exhibit an increased sensitivity to standard chemotherapy regimens and a more robust immunological microenvironment [32][33][34][35][36][37][38].…”
Section: Prognostically Significant Tumor Immune Biomarkersmentioning
confidence: 99%